INFLUENCE OF THE CATALYST ACIDITY ON THE HYDROCRACKING OF MINAS VACUUM DISTILLATE INTO MIDDLE DISTILLATE. - A.S. Nasution (Scientific Contributions Oil and Gas, 1986)
Hydrocracking process is probably the most versatile of modern petroleum process. This versatility has been achieved by the development of specific families of catalysts, of processing schemes designed to allow these catalysts to function efficiently and optimal refining relationships between hydrocracking and other refinery processes. A study was conducted to determine the hydrochocking of Minas vacuum distillate into middle distillate with the operating conditions : temperature: from 390Â° to 410Â°C pressure : 100 kg/cm2 and H2/HC ratio = 1000 lt/lt. A catatest unit operated in a continuous system was used in these experiments. The experimental data show that the conversion of the feedstock, the actuation energy and the product characteristics of" Minas vacuum distillate hydrocracking depended on the operating temperature and the acidity of the catalyst, And low acidity of Ni-Mo/Al2 03SiO2 catalyst produce a high selectivity of middle distillare.